2004
DOI: 10.1146/annurev.immunol.22.012703.104533
|View full text |Cite
|
Sign up to set email alerts
|

CD40/CD154 Interactions at the Interface of Tolerance and Immunity

Abstract: Development of the acquired immune response is dependent on the signaling of CD40 by its ligand, CD154. These molecules govern both the magnitude and quality of humoral- and cell-mediated immunity. A litany of studies have conclusively documented that blockade of this ligand-receptor pair can prevent, and also intervene in, the progression of antibody- and cell-mediated autoimmune diseases, and can instill long-lived allogeneic and xenogeneic graft tolerance. Many effector mechanisms of inflammation are abolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
478
1
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(501 citation statements)
references
References 146 publications
11
478
1
11
Order By: Relevance
“…Recent advances in immunology have shown that several types of molecules may be used as novel adjuvants to enhance immunogenicity of vaccines, such as cytokines, chemokines, Toll-like receptor ligands, and some costimulatory molecules [44][45][46][47]. Among these molecules, CD40L is attractive since it is one of the main mechanisms by which CD4 + T cells provide help to CTL and B cells [16,18,19,31]. The CD4 + T-cell-replacement activity of CD40L in our DC co-culture experiments is especially intriguing in the setting of development of a therapeutic vaccine for HIV-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in immunology have shown that several types of molecules may be used as novel adjuvants to enhance immunogenicity of vaccines, such as cytokines, chemokines, Toll-like receptor ligands, and some costimulatory molecules [44][45][46][47]. Among these molecules, CD40L is attractive since it is one of the main mechanisms by which CD4 + T cells provide help to CTL and B cells [16,18,19,31]. The CD4 + T-cell-replacement activity of CD40L in our DC co-culture experiments is especially intriguing in the setting of development of a therapeutic vaccine for HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Several members of tumor necrosis factor/tumor necrosis factor receptor superfamily (TNFSF/TNFRSF), including CD40L (CD154)/CD40, have been shown to enhance immunity by promoting expansion and survival of T, B, and dendritic cells (DCs) [15][16][17]. CD40L-CD40 interaction is considered as the main pathway through which CD4 + T cells provide help for the generation of CD8 + T cell responses and T cell dependent antibody responses [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the transcription factors activated by the TLR gene family, NF-B is a key regulator of the expression of molecules that mediate intercellular communication among leukocytes (9,10). TNF-␣ and CD40L can also activate the maturation process of DC, inducing signaling pathways mediated by TNFR or CD40 coupled TNFR-associated factor adaptors (11,12).…”
mentioning
confidence: 99%
“…CD40 belongs to the super-family of TNF receptors, and expression of CD40 is detected during early B cell ontogeny [27][28][29][30]. In mature B cells, signaling through CD40 promotes survival, somatic hyper-mutation and class-switch recombination, and the defective CD40 signaling results in hyper-IgM syndrome [31,32].…”
mentioning
confidence: 99%